2020
DOI: 10.1158/1078-0432.ccr-19-3790
|View full text |Cite
|
Sign up to set email alerts
|

DGKA Provides Platinum Resistance in Ovarian Cancer Through Activation of c-JUN–WEE1 Signaling

Abstract: Purpose: Although platinum compounds are the first-line treatment for ovarian cancer, the majority of patients relapse and develop resistance to treatment. However, the mechanism underlying resistance is unclear. The goal of our study is to decipher the mechanism by which a metabolic kinase, diacylglycerol kinase alpha (DGKA), confers platinum resistance in ovarian cancer.Experimental Design: Metabolic kinase RNAi synthetic lethal screening was used to identify a cisplatin resistance driver in ovarian cancer. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 48 publications
2
37
0
Order By: Relevance
“…In the same line, POLE gene damaging variants ( 129 ) and TP53 mutation ( 130 ) may also be correlated with the immunotherapeutic effect, this suggests that the combination of immune checkpoint inhibitor and certain pathway-targeted drugs may be a future direction for stratified therapy of EOVC patients. Besides, it’s reported that the DGKA-c-JUN-WEE1 signal pathway participates in the mechanism of platinum resistance in EOC patients ( 131 ), providing direction for targeted therapy to antagonize platinum resistance in the future study. Compared with effective but poorly tolerated concurrent therapy, Fang et al.…”
Section: Treatment and Potential Therapy Strategiesmentioning
confidence: 99%
“…In the same line, POLE gene damaging variants ( 129 ) and TP53 mutation ( 130 ) may also be correlated with the immunotherapeutic effect, this suggests that the combination of immune checkpoint inhibitor and certain pathway-targeted drugs may be a future direction for stratified therapy of EOVC patients. Besides, it’s reported that the DGKA-c-JUN-WEE1 signal pathway participates in the mechanism of platinum resistance in EOC patients ( 131 ), providing direction for targeted therapy to antagonize platinum resistance in the future study. Compared with effective but poorly tolerated concurrent therapy, Fang et al.…”
Section: Treatment and Potential Therapy Strategiesmentioning
confidence: 99%
“…Recent studies have shown that WEE1 is implicated in multidrug resistance, particularly to drugs related to cell cycle modulators, DNA‐damaging agents, or DNA‐repair inhibitors. Consistently, the drug resistance of tumors is associated with increased expression of WEE1 or activation of WEE1 signaling pathways 11,20 . Indeed, several reports have shown the synergistic effect of the WEE1 inhibitor with various anticancer agents in a variety of malignant diseases, such as the AURKA inhibitor alisertib (MLN8237) in HNSCC, 14 an ATR inhibitor in diffuse large B‐cell lymphoma, 15 a BET inhibitor in non‐small‐cell lung cancer, 35 trastuzumab in HER2‐positive breast cancer, 36 and avapritinib in gastrointestinal stromal tumors 20 .…”
Section: Discussionmentioning
confidence: 93%
“…Several reports have shown that the differential antitumor activity of the WEE1 inhibitor appears to be particularly dependent on TP53 mutation status 9‐11,14 . Given that TP53 is the most frequently altered gene in UC 18,19 and CDDP is the flagship drug for advanced UC, a synergistic antitumor effect of MK‐1775 and CDDP can be expected.…”
Section: Introductionmentioning
confidence: 99%
“…However, approximately 70% of ovarian cancer patients relapse after receiving cisplatin chemotherapy, 21 and the mechanism of cisplatin resistance in ovarian cancer is not clear. 22 In this study, we determined for the first time that LNC00115 is involved in the regulation of cisplatin resistance in ovarian cancer. Compared with that in the ovarian cancer cell line SKOV3, LNC00115 was more highly expressed in the ovarian cancer cisplatin-resistant cell line SKOV3-DDP.…”
Section: Discussionmentioning
confidence: 99%